Trends of the Political Commentary in the Egyptian Revolution - Shqair, Hadeel Sameer (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to understand the trends in political commentary on the Al Jazeera channel during the Egyptian Revolution and to obtain a clear and in-depth vision to clarify the description of the genre under which it falls between the concepts of political commentary and political analysis, and to identify the themes that emerged in the content and how they were concentrated under specific main classifications. Methods: The study followed the thematic analysis approach, based on analyzing the themes of the archival content of political commentary presented by Azmi Bishara on the Al Jazeera News Channel during the eighteen days of the Egyptian Revolution in 2011. Results: The results indicated that what Azmi Bishara presented on Al Jazeera during the Egyptian Revolution was not just political analysis, but rather, with its warning, encouraging, and directive content, it served as a guide for the revolution based on Bishara’s political views. Conclusion: This study paves the way for future research aimed at studying the details of news commentary presented on television news channels, in various fields, such as military commentary, economic commentary, and political commentary, which is often characterized by the distinctiveness of the personalities who present it, and studying the extent of the influence it has on the audience.